Pengaruh Video Kesehatan Reproduksi Terhadap Pengetahuan Remaja Putri Tentang Bahaya Kehamilan Usia Dini di Wilayah Kerja Puskesmas Singkawang Utara 1 - Lily Yuniar Yuniar; Erni Juniartati; Niya Fittarsih (Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescence is the transition between childhood and adulthood, characterized by unstable emotions and a high level of curiosity. This study aims to evaluate the effectiveness of education through video and leaflet media in increasing the knowledge of adolescent girls about the dangers of early pregnancy. The research design is quasi-experimental with a pretest-posttest and control group. The intervention group received education through video, while the control group received education through leaflets. Results showed a significant increase in knowledge in both groups. In the intervention group, the p value was < 0.000, while in the control group, it was 0.003. The average increase in knowledge in the intervention group was 17.00, and in the control group, it was 11.00. In conclusion, there is a significant impact of education through video on the knowledge of adolescent girls about the dangers of early pregnancy.